Food Specialization of the Lesser Grain Borer, Rhyzopertha Dominica F. (Coleoptera: Bostrichidae) - Obretenchev, Doncho; Zidan, Firas; Atanasova, Daniela (Canadian Journal of Agriculture and Crops, 2020)
Observations of stored grain, products from its manufacture and materials from plant origin in the storage-silo bases in Bulgaria were conducted from 1990 till 2019 to establish the food specialization and trophic chains of Rhyzopertha dominica F. The insect was found mostly in wheat grain – 49,2% from all expected samples, followed by barley – 18,5% and maize – 15,2%. The infestation of oats, rye, rice, and sorghum was 7.3%, 5.7%, 2.6%, and 1.5%, respectively. R. dominica infested also seeds of sugar and technical cane, millet, buckwheat, ryegrass, and Dactylis glomerata L. It was established in roots and fruits of Ecbalium elaterium L., roots of wild pumpkin – Bryonia alba L., bark of Frangula alnus Mill., crashed fruits of Aesculus hippocastanum L., fruits of Paleurus aculeatus L., seeds of quinoa Chenopodium quinoa, seeds of Trigonella foenum-grecum, seeds of Hibiscus cannabinus, seeds of Beta vulgaris L. and also in grain foods like "Kus-Kus". R. dominica did not develop in dried beans, lentil, edible and forage peas, vetch, chick-peas, soy, alfalfa, and clover. It was not found in storages with sunflower, rape, and coriander, and kernels - peanuts, groundnuts, hazelnuts, almond, sesame and pumpkins seeds.